2005
DOI: 10.1258/1357633054893373
|View full text |Cite
|
Sign up to set email alerts
|

Teleradiology and emerging business models

Abstract: A number of new diagnostic radiology services have emerged which use teleradiology. The main themes include: (1) stand-alone teleradiology practice; (2) the "Nighthawk"/on-call coverage; (3) solo radiologist practice; (4) expert/second-opinion teleradiology; (5) a global virtual radiology service based on workload sharing and reallocation. More applications of teleradiology can be expected due to the continuing shortages and uneven distribution of radiologists, and the increasing use of radiological imaging fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 0 publications
0
19
0
Order By: Relevance
“…general practitioners, insurance companies, and governmental departments, requires a monitoring framework to enable synchronization of processes and to check collaboration agreement adherence (and to act upon it) [6]. Within the healthcare domain, teleradiology is an already well-established area in which collaborations between different organizations is commonplace and succesful [23,45,57], although collaborations are usually considered to be static. In our view, collaborations (and thus agreements) should be established much more dynamically.…”
Section: Case Study: Teleradiology As An Evolving Business Networkmentioning
confidence: 99%
“…general practitioners, insurance companies, and governmental departments, requires a monitoring framework to enable synchronization of processes and to check collaboration agreement adherence (and to act upon it) [6]. Within the healthcare domain, teleradiology is an already well-established area in which collaborations between different organizations is commonplace and succesful [23,45,57], although collaborations are usually considered to be static. In our view, collaborations (and thus agreements) should be established much more dynamically.…”
Section: Case Study: Teleradiology As An Evolving Business Networkmentioning
confidence: 99%
“…However the main challenge is seamless integration of teleradiology with PACS, in order to enable flexible exchange of patient related information, i.e. electronic patient records (EPR) and radiological images including priors [2, 5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…Different models for the usage of teleradiology can be defined accordingly: (1) a single facility (hospital or imaging centre) using teleradiology for on-call purposes (home-based radiologists); for obtaining expert/second opinions; or for outsourcing the readings to an outside teleradiology company or hospital, (2) an enterprise with multiple facilities, using teleradiology for in-house distribution of workload, for obtaining second/expert opinions or for outsourcing the work to a commercial teleradiology provider, (3) a radiology group or teleradiology company providing professional services to several related or unrelated facilities (in terms of ownership) [2, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…7,10 The participants also stated that a lack of contact with the radiologist is likely to impede the diagnostic progress of the patients, particularly in emergency cases. 13,14 These problems are serious threats for the effectivity and quality of teleradiology practices. Our results also suggested that the integration of accurate clinical history is of prime importance for the efficiency of teleradiology consultations.…”
Section: 7-9mentioning
confidence: 99%